Analisis fonologis pada rekaman tartil surah Asy-Syams: Kajian asimilasi, dismilasi, dan fenomena suprasegmental - Sholichin, Muhammad Sulthonus (Maliki Interdisciplinary Journal, 2025)
The Qur’an, as the revelation of Allah SWT, possesses uniqueness not only in its semantic layer but also in its phonetic structure. A phonological study of tartil recitation is essential to understand the principles underlying its clarity, precision, and auditory beauty. This research aims to identify and analyze phenomena of assimilation, dissimilation, and suprasegmental aspects in the tartil recitation of Surah Asy-Syams. Using a descriptive-analytical qualitative method, data was collected from recordings of proficient qari’ (reciters) and analyzed based on the frameworks of modern phonology and tajwid rules. The results reveal several key phenomena: a dissimilation process in the word دَسَّىهَا (the change from /s/ to /y/) to avoid a difficult gemination; ash-shamsiyyah assimilation of the article ال; a gemination process (Idghām Mutamāthilain); variations of tafkhīm and tarqīq affecting sound quality; and the regulation of vowel duration through the mad system. In conclusion, this study finds that tartil recitation constitutes a systematic realization of phonological principles integrated with tajwid rules, where the interaction between segmental and suprasegmental aspects shapes the accuracy, fluency, and aesthetic quality of Qur’anic recitation.